Eksplorasi Komitmen Perubahan Organisasi pada Penyuluh Keluarga Berencana: Peran Perilaku Mengambil Resiko sebagai Determinant dan Kompleksitas Tugas sebagai Variabel Mediasi - Fasni , Ahmad; Febrimeidori, Febrimeidori; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to analyze the impact of risk-taking behavior on the commitment to organizational change among family planning extension workers and to examine the mediating role of task complexity in this relationship. The research was conducted among family planning extension workers in Padang City, West Sumatra Province. The final sample consisted of seventy-seven family planning extension workers who were selected randomly. Data collection was carried out through questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that risk-taking behavior has a positive and significant effect on the commitment to organizational change among family planning extension workers. Additionally, task complexity was found to partially mediate the relationship between risk-taking behavior and commitment to organizational change. Higher levels of risk-taking behavior were associated with greater commitment to organizational change, with task complexity serving as a mediating variable. The implications of this study suggest the need to enhance risk-taking behavior and adaptation skills among family planning extension workers in order to address increasingly complex tasks and to foster their commitment to organizational change.